Strategi Pengembangan Keterampilan Teknologi Informasi Bagi Siswa SMK Terpadu ALTA Kabupaten Semarang - Prakasa Hadi, Andik; Dewi, Maya Utami; Siswanto, Siswanto; Kuncoro, Wreda Agung; Santoso, Agustinus Budi; Priyadi, Priyadi; Imaliya, Tri (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The development of knowledge in information technology significantly influences student learning, especially in entrepreneurship subjects, thus making various digital-based learning methods develop rapidly. Starting from the idea of a team of University of Science and Computer Technology (STEKOM) lecturers providing training to Alta Integrated Vocational High School students in Semarang Regency, which aims to increase competence in the field of information technology. The material is related to branding, google my business and google trends. Lecture methods and direct practice are used in this training activity with the concept of community service. The stages of this training consist of Registration, Activity, Output, and Evaluation. It is hoped that in the future this kind of activity can be held regularly and continuously.